PROFILE OF PHYSICAL CONDITION OF INDONESIAN JUNIOR BADMINTON ATHLETES - kosasih, Alam Hadi; Permana, Dian; Zinat, Irfan; Iskandar, Dedi (STKIP Muhammadiyah Kuningan, 2024)
The purpose of this study was to reveal the profile of the physical condition of Indonesian junior badminton athletes. Participants in this study were 40 badminton athletes (age = 14-18 years, Male = 31, Female = 9). Research instruments on physical conditions are endurance, strength & conditioning, speed, flexibility, and coordination. Data analysis with descriptive statistics. This study concludes the condition profile as follows; 1) Endurance in male athletes when viewed from an average of 60.29, then falls into the